Anti-obesity effect of crocin and ethanolic extract of saffron (Crocus sativus L.) in rats fed with high-fat diet - Mashmoul, Maryam (2017)
Obesity is one the most common nutritional disorder in the world which can increase the risk of numerous medical problems. Saffron, a source of bioactive compounds,recently has attracted interest for many health benefits.The aim of this study was to evaluate anti-obesity effects of saffron ethanolic extract and its most bioactive com-pound; crocin in animal model. Obesity was induced by feeding high-fat diet to male Sprague Dawlyrats for 12 weeks. Then the animals were divided into seven groups in which three of them served as controls; normal diet, high-fat diet, high-fat diet plus orlistat and the other four groups were treated with saffron extract and crocin at low and high doses (40 and 80 mg/kg/day) in their food for eight weeks. Changes in anthropometrical parameters and food intake were recorded. At the end of study blood samples were collected by cardiac puncture for biochemical analysis. The visceral fat pad were dissected and weighed and the liver, pancreas and kidney samples were re-moved to stain with hematoxylin & eosin (H&E) for histopathological examination. Results showed that crocin (80 mg/kg) significantly decreased the rate of body weight gain(0.09±0.01), totalvisceral fat pad(7.19±0.22)and weight ratio of epididymal fat to body(1.72±0.80)(p<0.05)compared with high-fat group while saffron extract (80 mg/kg) displayed a significant (p<0.01) reduction on food intake in experimental rats. Furthermore, crocin (80 mg/kg) significantly reduced plasma levels of triacylglyceride(TG)(1.86±0.29 mM/L)and total cholesterol (TC)(1.07±0.08 mM/L)compared with high-fat control group(p<0.05). Treatment with 80 mg/kg of saffron extract (p< 0.001) and crocin (p<0.05) on the obese rats significantly decreased fasting blood glucose level rather than orlistat. The plasma insulin and TNF-훼levels reduced significantly while catalase and adiponectin levels were increased markedly in groups treated with saffron extract and crocin at the high dose (80 mg/kg). Moreover, a significant increment in ghrelin (p<0.05) and decrement in leptin (p<0.05) were observed in crocin (80 mg/kg) treated group. Saffron extract and crocin dose dependently alleviated the level of liver enzymes in diet induced obese-rat model compared to high-fat diet fed group. Moreover semi-quantitative histological assessment of saffron extract and crocin supplementation on fatty liver tissue indicated that hepatic steatosis and ballooning significantly decreased by high dose of saffron extract (p<0.01) and crocin (p<0.05) treatments. In term of none-alcoholic fatty liver disease (NAFLD) activity score (NAS), saffron extracts dose dependently (p<0.01) and crocin 80 mg/kg (p<0.05) ameliorated the NAS value. Histopathological examination of kidney and pancreatic tissues of obese rats treated with crocin and saffron extract indicated that saffron extract at both doses exhibited similar protective effect against renal injuries in term of vascular congestion and interstitial inflammation induced by high-fat diet. High dose (80 mg/kg) of the saffron extract supplementation showed significant protective effect in reducing pancreatic adipose tissue infiltration (p<0.05). Overall anthropometrical, biochemical and histopathological outcomes suggest that saffron extract and crocin supplementations at thelevel of tested concentrations have anti-obesity property through enhancement of glucose and lipid metabolism, anti-inflammatory and regulatory effects of adipocytokines and protective effects against fatty liver and untoward impact of fatty diet in kidney and pancreatic tissues of diet-induced obese rats which are encouraging.